Relationship of udder morphometry with milk yield and body condition traits in Beetal goats - JENA, SOUMYASHREE; MALIK, D S; KASWAN, SANDEEP; SHARMA, AMIT; KASHYAP, NEERAJ; SINGH, UDEYBIR (The Indian Journal of Animal Sciences, 2019)
Present study was conducted to find the relationship of udder morphometry with milk yield and body condition traits in Beetal goats. Beetal goats (60) having 4 different parities were used. Udder (length, column width, row width, depth, circumference, volume) and teat (length, diameter, circumference, height from ground, inter teat distance) morphological traits were recorded just before morning milking at fortnightly interval up to 3 months post-kidding stage. Simultaneously, milk yield (morning and daily) and body condition parameters (body condition score (BCS), sternal and lumbar thickness) were also recorded. All the udder morphological traits were positively correlated with morning as well as daily milk yield. Similarly, teat morphological traits were also positively correlated with morning as well as daily milk yield except teat height from ground which had negative correlation. Whereas some of the udder and teat morphological traits showed positive correlation with body condition parameters. Milk yield had positive correlation with BCS, sternal and lumbar thickness. It can be concluded that the udder and teat morphological traits have direct relationship with milk yield and body condition parameters in Beetal goats.